Effects of transcranial magnetic stimulation on cerebellar ataxia: A systematic review and meta-analysis - Wang, Ying; Zhang, Di; Wang, Ju; Ma, Jiang; Lu, Li; Jin, Song (Frontiers in Neurology, 2023)
Abstract Objective: To determine the effectiveness of Transcranial Magnetic Stimulation improves cerebellar Ataxia Data sources: PubMed, EMBASE, the Cochrane Library, Springer, Science Direct, CNKI, VIP were searched until 2022. Review methods: Trials with Transcranial Magnetic Stimulation on the effects on cerebellar Ataxia were included, and the effect size was evaluated by using the standardized mean difference (SMD) or mean difference (MD) and a 95% confidence interval (CI). Results: Eight studies with 272 participants were published between 2014 and 2022 were included, the effect of TMS on ICRAS (P<0.01, I2=4%), SARA (P<0.01, I2=27%), BBS (P<0.01, I2=0%), TUG (P<0.01, I2 =0%) in cerebellar Ataxia patients was significant. Conclusion: The effects of Transcranial Magnetic Stimulation improving cerebellar Ataxia patients is significant, TMS targeting cerebellar structures can induce changes in the excitability of cerebellar-thalamus-cortical pathways, it is necessary to carry out large-scale research with good design and high quality in the future. Keywords cerebellar Ataxias, Hereditary Ataxias; Spinocerebellar Ataxias, Transcranial Magnetic Stimulation, systematic review, Treatment, meta-analysis